2020
DOI: 10.1088/1757-899x/933/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Slope stability analysis using Bishop and Finite Element Methods

Abstract: Analysis of slope stability in this study aims to determine the safety factor (SF) of the landslide for the existing and the reinforcement condition. The study case was in STA 84+910 of national road Meulaboh-Geumpang, West Aceh Regency in Aceh Province. The condition of the Meulaboh-Geumpang road often causes landslides due to the topography of the area and is also triggered by rainfall. The analysis of safety factor for the existing condition was calculated by using the Bishop method that assumes a circular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The result found that, with an increase in the height of the slopes, the factor of safety decreased. Various authors have conducted soil slope analyses based on different parameters and reported improved results [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result found that, with an increase in the height of the slopes, the factor of safety decreased. Various authors have conducted soil slope analyses based on different parameters and reported improved results [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The model was successfully implemented in a finite element code, and its performance was demonstrated through various numerical examples. Sungkar et al [19] conducted a slope stability analysis using both Bishop and FEM. The study evaluates the safety factor of a landslideprone area on a national road.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of slope stability is very much needed in developing the current use of slopes [2]. Due to the increasing use of slopes for the benefit of mankind, it is necessary to develop the concept of slope stability to overcome the problem of landslides on slopes [3].…”
Section: Introductionmentioning
confidence: 99%
“…We employ the Limit Equilibrium Method (LEM) and Finite Element Method (FEM) to comprehensively evaluate safety factor results, comparing empirical and numerical calculations for slope stability. The Finite Element Method (FEM) is a precise and versatile approach that eliminates the need for assumptions regarding the type of slope failure ( (Sungkar et al, 2020). In this study, FEM is employed to assess both the magnitude and direction of soil displacement caused by landslides, validating the obtained safety factor.…”
Section: Introductionmentioning
confidence: 99%